Never judge a book by its cover: a sociological examination of body art - Teeter, Allison M. (Kansas State University, 2008)
In recent years body modification practices such as the arts of tattooing and body piercing have experienced an increase in popularity. A close examination of previous research conducted on the topic revealed a dichotomous categorization of these practices as either acts of deviance or self-expression. In an effort to add to the research that strives to portray 'body art' as a means of identity formation, the current study took a qualitative approach to the examination of body modification practices and the individuals who participate in them. Throughout 2007, fifteen in-depth interviews were conducted with college-age individuals who had at least one visible piece of 'body art,' and were currently living in or around Manhattan, Kansas. An emphasis was placed on what motivated the individuals to participate in the arts of tattooing and/or body piercing and how they felt the physical alteration of their body had affected their subsequent social interactions and identity. A careful review of the interview transcripts revealed that the respondents had chosen to participate in body modification practices for a variety of reasons. Nine analytical categories were then created in an attempt to explain the key motivations for their participation in these practices and ultimately call into question whether these practices should continue to be viewed as "deviant." The findings also demonstrated that there is still a certain amount of stigma associated with the arts of tattooing and body piercing, especially within the workplace. Although some businesses and organizations require their employees to keep their artwork concealed during business hours, others simply refuse to hire any individual who has a visible piece of 'body art.' Thus, the knowledge gained from the respondents and their experiences provided insight into the thought processes involved in the decision to participate in body modification practices as well as shed light on discriminatory, appearance-based hiring practices.
Keywords: Body art; Body modification; Motives for participation in arts of tattooing and body piercing; Stigma; Sociology, General (0626)